Effect of repaglinid on ovariectomy induced bone loss in rats: comparison with 17?-estradiol - Ulas, Mustafa (My University, 2017)
Aim: The aim of this study was to investigate the effect of repaglinide (RPG), anti-diabetic drug used commonly diabetic patients, on bone loss ovariectomized (OVX) rats”.Material and Methods: Forty Wistar albino rats were equally divided into five groups as follows: Group 1, control, non-OVX rats; Group 2, OVX rats administered 0.1 % ethanol; Group 3, OVX rats administered subcutan 17?-estradiol (E2) at a dose of 40 µg/kg; Group 4, OVX rats administered oral RPG at a dose of 0.5 mg/kg; Group 5, OVX rats administered E2 (40 µg/kg) and RPG (0.5 mg/kg) rats. Administration of drugs started 5 days after bilateral ovariectomy and continued for 35 days. After 35 days of treatment, the animals were sacrificed and the whole femurs were dissected and were analyzed for bone mineral density (BMD) and bone mineral content (BMC) by dual-energy x-ray absorptiometry (DXA).Results: There were no significant difference between OVX and RPG groups for BMC and BMD values. Compared with the OVX groups, E2 administration of OVX groups had higher BMC but no significant difference for BMD. OVX group had significantly lower value than the control group.Conclusion: RPG administrated to OVX rats for 35 days had no beneficial effect on bone loss status in OVX rats.
Keywords: Kadın Hastalıkları ve Doğum; Endokrinoloji ve Metabolizma; Genel ve Dahili Tıp; Romatoloji